Intestinal Malrotation with Midgut Volvulus Comorbidity with Bronchopneumonia: A Case Report - Fatmah Sindi; Yusri Dianne Jurnalis; Jon Effendi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Intestinal malrotation is a congenital anomaly resulting from abnormal rotation and fixation of an imperfect midgut during embryonic development. This study aims to describe the diagnosis and management of intestinal malrotation and its comorbid diseases in children. Case presentation: A boy, aged 9 months, was referred from a regional hospital with complaints of repeated vomiting accompanied by a distended stomach and no bowel movements for 4 days. Based on the birth history, the patient was born with vacuum assistance for the indication of prolonged phase II. The results of the physical examination showed that the patient was seriously ill, with compos mentis, pulse rate 130 x/minute, respiratory rate 34x/minute, blood pressure 90/60 mmHg, temperature 37.6ºC, 99% saturation with the help of O2 nasal canule 2L/minute. There are increased bowel sounds on abdominal examination. Blood examination showed an increase in leukocytes (10.850/mm3). The chest X-ray showed lateral bronchopneumonia, and the abdominal X-ray showed low-lying obstructive ileus. The patient was diagnosed with obstructive ileus due to volvulus, moderate dehydration, comorbid with bronchopneumonia, and global developmental delay. Conclusion: Management of intestinal malrotation with volvulus in this patient includes general improvement and rehydration, Ladd's procedure for definitive correction of the cause. Management of comorbid global developmental delay is carried out after the emergency is resolved.